Security theology, surveillance and the politics of fear / Nadera Shalhoub-Kevorkian. - Shalhūb-Kīfūrkiyān, Nādirah (Cambridge studies in law and society., 2015)
This examination of Palestinian experiences of life and death within the context of Israeli settler colonialism broadens the analytical horizon to include those who 'keep on existing' and explores how Israeli theologies and ideologies of security, surveillance and fear can obscure violence and power dynamics while perpetuating existing power structures. Drawing from everyday aspects of Palestinian victimization, survival, life and death, and moving between the local and the global, Nadera Shalhoub-Kevorkian introduces and defines her notion of 'Israeli security theology' and the politics of fear within Palestine/Israel. She relies on a feminist analysis, invoking the intimate politics of the everyday and centering the Palestinian body, family life, memory and memorialization, birth and death as critical sites from which to examine the settler colonial state's machineries of surveillance which produce and maintain a political economy of fear that justifies colonial violence.